2022
DOI: 10.1002/suco.202100280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concrete wet packing density on the uni‐axial strength of manufactured sand CFST columns

Abstract: River sand (RS) has been the most popular fine aggregate in concrete production. Recently, because of the continuing decline in supply of RS, alternative source of fine aggregates is needed. Manufactured sand (MS), which is produced by mechanical crushing of virgin rock or construction waste, is becoming more popular for replacing RS. Concrete containing MS has higher compressive strength but is more brittle. To promote the application of MS in concrete, concrete‐filled‐steel‐tube (CFST) column is advocated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The greatest decrease in strength was noted for mortars made with the higher-grade cement CEM 52.5. This showed that as the compressive strength increased, the cement matrix became more brittle, resulting in a decrease in flexural strength [ 36 , 37 ]. In addition, the introduced slag, due to its porous structure, weakened the contact zone between the aggregate and the cement binder, resulting in a decrease in mechanical performance.…”
Section: Resultsmentioning
confidence: 99%
“…The greatest decrease in strength was noted for mortars made with the higher-grade cement CEM 52.5. This showed that as the compressive strength increased, the cement matrix became more brittle, resulting in a decrease in flexural strength [ 36 , 37 ]. In addition, the introduced slag, due to its porous structure, weakened the contact zone between the aggregate and the cement binder, resulting in a decrease in mechanical performance.…”
Section: Resultsmentioning
confidence: 99%
“…However, when the fineness modulus is larger, an overall increasing trend is observed. Rubber particles distribute homogenously in the cementitious system and filling the voids between aggregates, resulting in larger apparent density and higher strength 65‐68 …”
Section: Resultsmentioning
confidence: 99%
“…Rubber particles distribute homogenously in the cementitious system and filling the voids between aggregates, resulting in larger apparent density and higher strength. [65][66][67][68]…”
Section: Fineness Modulus Of Combined Fine Aggregatementioning
confidence: 99%
“…The DSC exam is a technique used to measure the temperature and heat flow associated with phase transition temperatures of materials. (27,28) The DSC test of prepared samples was conducted in order to understanding the thermal behavior of the samples. Figure 7 shown the DSC curves of pure PMMA and PMMA enhanced with (0,02) PVA nanofibers and the results of Tg and T decomposition were listed in table 2.…”
Section: Thermal Characterizations Differential Scanning Calorimetry ...mentioning
confidence: 99%